MENINGKATKAN PARTISIPASI MAHASISWA DALAM DISKUSI KELAS MELALUI PENGGUNAAN FACEBOOK - Dwi Agustina; Susanto . (LPPM Universitas Pekalongan, 2011)
This research focuses on finding out the students’ participation in Drama class of English Department at Pekalongan University. This research was conducted due to the low participation of the students in the discussions. To overcome this matter, the writer conducted a classroom action research especially by using facebook to enhance the students’ participation in the discussion in Drama class. Key words: facebook, discussion, Drama